The genome sequence of the Large Nutmeg, Apamea anceps (Denis & Schiffermüller, 1775) - Holland, PWH (F1000 Research Ltd, 2024)
We present a genome assembly from an individual male Apamea anceps (the Large Nutmeg; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence is 615.8 megabases in span. Most of the assembly is scaffolded into 31 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 16.43 kilobases in length.